The emergence of carbapenemase-producing Enterobacterales in hospitals: a major challenge for a debilitated healthcare system in Lebanon - Daaboul, Dina; Oueslati, Saoussen; Rima, Mariam; Kassem, Issmat I.; Mallat, Hassan; Birer, Aurélien; Girlich, Delphine; Hamze, Monzer; Dabboussi, Fouad; Osman, Marwan; Naas, Thierry (Frontiers in Public Health, 2023)
Background Carbapenem- and extended-spectrum cephalosporin-resistant Enterobacterales (CR-E and ESCR-E, respectively) are increasingly isolated worldwide. Information about these bacteria is sporadic in Lebanon and generally relies on conventional diagnostic methods, which is detrimental for a country that is struggling with an unprecedented economic crisis and a collapsing public health system. Here, CR-E isolates from different Lebanese hospitals were characterized. Materials and methods Non-duplicate clinical ESCR-E or CR-E isolates (N = 188) were collected from three hospitals from June 2019 to December 2020. Isolates were identified by MALDI-TOF, and their antibiotic susceptibility by Kirby-Bauer disk diffusion assay. CR-E isolates (n = 33/188) were further analyzed using Illumina-based WGS to identify resistome, MLST, and plasmid types. Additionally, the genetic relatedness of the CR-E isolates was evaluated using an Infrared Biotyper system and compared to WGS. Results Using the Kirby-Bauer disk diffusion assay, only 90 isolates out of the 188 isolates that were collected based on their initial routine susceptibility profile by the three participating hospitals could be confirmed as ESCR-E or CR-E isolates and were included in this study. This collection comprised E. coli (n = 70; 77.8%), K. pneumoniae (n = 13; 14.4%), Enterobacter spp. (n = 6; 6.7%), and Proteus mirabilis (n = 1; 1.1%). While 57 were only ESBL producers the remaining 33 isolates (i.e., 26 E. coli, five K. pneumoniae, one E. cloacae, and one Enterobacter hormaechei) were resistant to at least one carbapenem, of which 20 were also ESBL-producers. Among the 33 CR-E, five different carbapenemase determinants were identified: blaNDM-5 (14/33), blaOXA-244 (10/33), blaOXA-48 (5/33), blaNDM-1 (3/33), and blaOXA-181 (1/33) genes. Notably, 20 CR-E isolates were also ESBL-producers. The analysis of the genetic relatedness revealed a substantial genetic diversity among CR-E isolates, suggesting evolution and transmission from various sources. Conclusion This study highlighted the emergence and broad dissemination of blaNDM-5 and blaOXA-244 genes in Lebanese clinical settings. The weak AMR awareness in the Lebanese community and the ongoing economic and healthcare challenges have spurred self-medication practices. Our findings highlight an urgent need for transformative approaches to combat antimicrobial resistance in both community and hospital settings.